Moschamine inhibits proliferation of glioblastoma cells via cell cycle arrest and apoptosis. Issue 5 (April 2017) - Alexiou, George A; Lazari, Diamanto; Markopoulos, Georgios; Vartholomatos, Evrysthenis; Hodaj, Entela; Galani, Vasiliki; Kyritsis, Athanasios P
Glioblastoma is the most common and most malignant primary brain tumor with a median survival of 15 months. Moschamine is an indole alkaloid that has a serotoninergic and cyclooxygenase inhibitory effect. In this study, we sought to determine whether moschamine could exert cytotoxic and cytostatic effects on glioma cells in vitro. Moschamine was tested for toxicity in zebrafish. We investigated the effect of moschamine on U251MG and T98G glioblastoma cell lines. Viability and proliferation of the cells were examined with trypan blue exclusion assay, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay, and the xCELLigence system. Apoptosis (annexin–propidium iodide), cell cycle, and CD24/CD44/CD56/CD15 expression were tested with flow cytometry. Treatment with moschamine significantly reduced cell viability in both cell lines tested. Induction of cell death and cell cycle arrest was confirmed with flow cytometry in both cell lines. After treatment with moschamine, there was a dose-dependent decrease in CD24 and CD44 expression, whereas there was no change in CD56 and CD15 expression in T98G cell line. The zebrafish mortality on the fifth post-fertilization day was zero even for 1 mM of moschamine concentration. The treatment of glioblastoma cell lines with moschamine may represent a novel strategy for targeting glioblastoma.